Pembentukan Karakter Disiplin Siswa melalui Lingkungan Sekolah - Tri Purwati; Chairunissa; Arlin Nurmaliani; Yodi Ahmad Sirojudin; Reczy Setian Suharno; Mumuh; Rohendi Ali; Nana Herdiana Abdurrahman; Revita Yanuarsari (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Student character development is one of the primary goals of education, playing a crucial role in shaping students' personalities, attitudes, and behaviors to align with the nation's moral, social, and cultural values. Discipline is one of these traits. The school environment plays a strategic role as a place for character development because schools serve not only as a place to transfer knowledge but also as a place to cultivate character values ​​through school culture, the role models and roles of teachers, and social interactions between students. This article aims to examine the role of the school environment in developing students' disciplined character based on the results of a review of various relevant literature sources. The method used in writing this article is a literature study, collecting, reviewing, and analyzing various journal articles related to character education and the school environment. The results of the study indicate that a conducive school environment, supported by a positive school culture, consistent implementation of discipline, role models and the role of educators, and learning and extracurricular activities integrated with character values, influences the development of student character development. Therefore, managing the school environment oriented towards strengthening character values ​​needs to be a crucial aspect in the implementation of education. Keywords: character development, school environment, character education Abstrak Pembentukan karakter siswa merupakan salah satu tujuan utama pendidikan yang berperan penting dalam membentuk kepribadian, sikap, dan perilaku siswa agar sesuai dengan nilai-nilai moral, sosial, dan budaya bangsa. Salah satunya yaitu karakter disiplin. Lingkungan sekolah memiliki peran strategis sebagai tempat pembinaan karakter karena sekolah tidak hanya berfungsi sebagai tempat untuk mentransfer pengetahuan, tetapi juga sebagai tempat pembiasaan nilai-nilai karakter melalui budaya sekolah, keteladanan dan peran guru, serta interaksi sosial antarsiswa. Artikel ini bertujuan untuk mengkaji peran lingkungan sekolah dalam pembentukan karakter disiplin siswa berdasarkan hasil kajian dari berbagai sumber literatur yang relevan. Metode yang digunakan dalam penulisan artikel ini adalah studi pustaka (studi literatur) dengan mengumpulkan, menelaah, dan menganalisis berbagai artikel jurnal yang berkaitan dengan pendidikan karakter dan lingkungan sekolah. Hasil kajian menunjukkan bahwa lingkungan sekolah yang kondusif, didukung oleh budaya sekolah yang positif, penerapan disiplin yang konsisten, keteladanan dan peran pendidik, serta kegiatan pembelajaran dan ekstrakurikuler yang terintegrasi nilai-nilai karakter, berpengaruh dalam perkembangan pembentukan karakter siswa. Oleh karena itu, pengelolaan lingkungan sekolah yang berorientasi pada penguatan nilai karakter perlu menjadi perihal penting dalam penyelenggaraan pendidikan. Kata kunci: pembentukan karakter, lingkungan sekolah, pendidikan karakter